Clinical binge eating, but not uncontrolled eating, is associated with differences in executive functions: Evidence from meta-analytic findings. (June 2021) - Prunell-Castañé, Anna; Jurado, María Ángeles; García-García, Isabel
Highlights: To study the relationship between executive functions and binge eating behaviors. Executive functions do not differ along non-clinical binge eating patterns. Binge eating disorder might be related with small deficits in executive function. Mood disorders linked with severe binge eating might influence cognitive deficits. Abstract: Introduction: Binge eating disorder (BED) is a common psychiatric diagnosis characterized by the presence of episodes of loss of control over food consumption. Understanding the neurocognitive factors associated with binge eating pathology might help to design clinical strategies aimed at preventing or treating BED. However, results in the field are notably heterogeneous. In the current study, we aimed to establish whether binge eating behaviors (both at a clinical and at a non-clinical level) are associated with executive functions. Methods: We performed a pre-registered meta -analysis to examine the link between executive functions, BED, and uncontrolled eating, a psychobiological construct closely associated with binge eating behaviors. Articles were searched on PubMed and the main exclusion criteria were lack of information about participants' age or sex distribution or adiposity measurements, studies performed in older populations (age > 65 years old) or studies including participants with purging symptoms. Results: Relative to healthy controls, patients with BED showed lower performance in executive functions, with a small effect size. At the same time, uncontrolled eating patterns were not associated with differences in executive functions. Neither age nor body mass index (BMI) influenced these results. Conclusions: Our findings suggest that there is no association between performance in executive functions and variations along the non-clinical spectrum of binge eating behaviors. Small deficits in executive functions, however, seem to appear in individuals showing severe binge eating symptoms, that is, individuals meeting diagnostic criteria for BED. We speculate that the close links between BED and emotional distress could partly explain these results.